IDENTIFICATION OF UDP-GLUCURONOSYLTRANSFERASE 1A10 IN NON-MALIGNANT AND MALIGNANT HUMAN BREAST TISSUES - Starlard-Davenport, Athena (2008)
UGT1A10 was recently identified as the major isoform that conjugates estrogens. In this study, real-time PCR revealed high levels of UGT1A10 and UGT2B7 in human breast tissues. The expression of UGT1A10 in breast was a novel finding. UGT1A10 and UGT2B7 mRNAs were differentially expressed among normal and malignant specimens. Their overall expression was significantly decreased in breast carcinomas as compared to normal breast specimens (UGT1A10: 68 ± 26 vs. 252 ± 86, respectively; p < 0.05) and (UGT2B7: 1.4 ± 0.7 vs. 12 ± 4, respectively; p < 0.05). Interestingly, in African American women, UGT1A10 expression was significantly decreased in breast carcinomas in comparison to normals (57 ± 35 vs. 397 ± 152, respectively; p < 0.05). Among Caucasian women, UGT2B7 was significantly decreased in breast carcinomas in comparison to normals (1.1 ± 0.5 vs. 13.5 ± 6, respectively; p < 0.05). Glucuronidation of 4-OHE(1) was significantly reduced in breast carcinomas compared to normals (30 ± 15 vs. 106 ± 31, respectively; p < 0.05). Differential down-regulation of UGT1A10 and UGT2B7 mRNA, protein, and activity in breast carcinomas compared to the adjacent normal breast specimens from the same donor were also found. These data illustrate the novel finding of UGT1A10 in human breast and confirm the expression of UGT2B7. Significant individual variation and down-regulation of expression in breast carcinomas of both isoforms was also demonstrated. These findings provide evidence that decreased UGT expression and activity could result in the promotion of carcinogenesis.